An economic analysis of productivity in organ transplantation in Brazil just before and after the COVID-19 pandemic - Alexandre Marinho (Archives of Organ Transplantation - Peertechz Publications, 2023)
We evaluate the productivity of the Brazilian states and the Federal District in transforming potential organ donors into actual donations in the years immediately before and after the COVID-19 pandemic (2019-2022). The Brazilian National Health System (SUS) which is one of the largest public transplant systems in the world, provides full coverage of all costs involved in organ donation, transplants, and post-transplant. We applied Ordinary Least Squares Regression in data from 2019-2022 and the results indicate that there is significant room for improvement in terms of converting potential donors into actual donors. The number of donors with organs transplanted decreased during the pandemic as the productivity of the transplant was affected, although it seems that the structure of the Brazilian transplant system and its technology were not significantly affected permanently.